(untitled) (International Seven Journal of Multidisciplinary, 2024)
Over the last 70 years, the world has made great strides in terms of human rights guarantees, and Brazilian legislation has not lagged behind. Today, with the Federal Constitution, the Refugee Law (Law No. 9,474/1997) and the new immigration law (Law No. 13,445/2017), Brazil has consolidated one of the most complete, modern and generous legal systems in the world for welcoming migrants, refugees and stateless people. These conditions mean that many people seek refuge in the country to receive humanitarian aid and establish their residence. Through bibliographic and documentary analysis, based on empirical theoretical knowledge, the work sought to discuss the process of Public Management practiced by the State, in particular the City of Curitiba through the MigraCidades Diagnostic Report/2021. It concluded that at the state level, public policies applied to migrants and refugees are managed through CERMA/PR with the support of organized civil society and pointed out shortcomings. At the municipal level, the public policies applied to migrants and refugees are managed by FAS with the support of organized civil society and pointed out shortcomings.